Stroma-Rich Variant of Castleman Disease Mimicking Retroperitoneal Malign Tumor: Case Report (Annals of Medical Research, 2021)
None
Keywords: Castleman’s Disease, Stroma-Rich Hyaline Vascular Type, Retroperitoneal Tumor